Pemanfaatan User Experience Questionare Dalam Analisis Pengalaman Pengguna MyBSI E-Learning System - Syamsiah, Nurfia Oktaviani; Purwandani, Indah; Nurwahyuni, Siti; Rosmiati, Mia (MULTINETICS, 2023)
The purpose of this study is to utilize User Experience Questionnaire (UEQ) to measure the user experience of learning management system. 201 respondents were involved as UEQ respondents with diverse backgrounds as system users. In this research, My BSI Elearning System (MYBEST) is used as the research object. MYBEST has various features for the process of teaching and learning activities starting from the attendance process, discussion, provision of learning materials both in the form of modules and video links, submitting assignments, conducting quizzes and monitoring attendance at previous meetings. This research will provide benefits for UX practitioners, educators and developers of online learning management systems. The findings in this research are also expected to provide benefits for all scope of actors in the world of education who implement computer-based teaching and learning activities. The results of MYBEST user experience evaluation using UEQ can be seen from the calculated aspects such as Attractiveness, Pragmatic Quality and Hedonic Quality. The resulting MYBEST UX evaluation value is quite satisfactory, where of the six scales observed, three of them got above average results, and the other three got good results. In this study, it was found that the pragmatic aspect of UEQ has a more dominant value than the hedonic aspect.